Mechanistic investigation on Ce addition in tuning recrystallization behavior and mechanical property of Mg alloy. (1st January 2023) - Li, J.R.; Xie, D.S.; Zeng, Z.R.; Song, B.; Xie, H.B.; Pei, R.S.; Pan, H.C.; Ren, Y.P.; Qin, G.W.
Highlights: The whole microstructural evolution during extrusion of Mg-Ce alloy was uncovered in this work. Profuse < c + a > dislocations have been activated in Mg-Ce alloy, which is different from < a > dislocations formed in pure Mg. The LAGB formation process related to < c + a > dislocations movement was directly observed by EBSD and TEM images. A novel Mg-Ce wrought alloy with high strength-ductility synergy has been obtained. Abstract: Constructing bimodal grain structure is a promising approach to achieve the high strength-ductility synergy in Mg alloy. Formation of bimodal grain is closely related to the dynamic and/or static recrystallization process, which has not been fully understood in the typical Mg-RE based alloy. In this work, it is claimed for the first time that the minor Ce addition (∼0.3 wt%) into Mg matrix significantly promotes the pyramidal and non-basal dislocations at the early stage of extrusion, which consequently enhances the formation of sub-grain boundaries via the movement and recovery of pyramidal II-type dislocations. At this stage, fine sub-grain lamellae are widely observed predominantly due to the low migration rate of sub-grain boundary caused by the limited mobility of dislocations. At the later stage, the sub-grains continuously transform into dynamic recrystallized (DRXed) grains that have 〈 10 1 ¯ 0 〉 Taylor axis and also strong fiber texture, indicating substantial activation of pyramidal II-type dislocation. The low mobility of dislocations, accompanied with the solute drag from grain boundary (GB) segregation and pinning from nano-phases, cause a sluggish DRX process and thus a bimodal microstructure with ultra-fined DRXed grains, ∼0.51 µm. The resultant texture hardening and grain refinement hardening effects, originated from bimodal microstructure, result in a yield strength of ∼352 MPa, which is exceptional in Mg-Ce dilute alloy. This work clarifies the critical role of Ce addition in tuning recrystallization behavior and mechanical property of magnesium, and can also shed light on designing the other high-performance Mg alloys.